Analysis Of The Influence Of Family Ownership, Corporate Governance, Company Size And Gender Diversity On Tax Aggressivity Of Mining Companies In Indonesia - Ratnawita, Ratnawita; Dheri Febiyani Lestari; Muhamad Risal Tawil; Muhammad Irsyad Elfin Mujtaba; Ngurah Pandji Mertha Agung Durya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
Using corporate governance as a moderating variable, this study attempts to examine the effects of firm size, institutional ownership, family ownership, and gender diversity on tax aggression. This study uses quantitative methods. The IDX-registered mining and CPO enterprises make up the study's population. Purposive sampling was the method employed by the researcher to choose the sample gathering strategy. Through documentation and a review of the literature, the researcher gathered data for this investigation. The data analysis approach employs hypothesis testing, data quality testing, and descriptive statistics based on the goals of the research. The study's findings provide important new information about the variables influencing tax aggressiveness in the corporate setting. First, the study shows that tax aggression is highly influenced by the size of the company. Second, corporate tax aggression is significantly shaped by institutional ownership. Furthermore, it has been demonstrated that family ownership affects tax aggression. Findings, however, indicate that management decisions about tax aggressiveness are not significantly impacted by gender diversity. It's interesting to note that the effects of corporate governance differ according to the independent variables that are measured. Corporate governance cannot increase the impact of gender diversity or family ownership on tax aggression, but it also cannot increase the impact of firm size. Corporate governance, however, has the power to amplify institutional ownership. These findings provide in-depth insight into the complexity of factors that influence tax aggressiveness practices in companies and can be a basis for developing management strategies and company policies in the future.